Pregnancy with Bidirectional Dominant Left-To-Right Shunt due to Ventricular Septal Defect and Large Secundum Atrial Septal Defect with Left-To-Right Shunt: A Case Report - Destikatari, Lovin; Prasetyorini, Nugrahanti; Putri, Valerinna Yogibuana Swastika (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Congenital heart disease (CHD) is the most common birth defect in humans, affecting approximately 0.8% of all live births. The spectrum of defects is broad, ranging from complex defects that lead to severe disability and death in infancy, to mild defects that may only be discovered later in asymptomatic adults. Case Presentation: This case report discusses a 21-year-old female in her second pregnancy was diagnosed with complex congenital heart disease after presenting with shortness of breath. Pulmonary hypertension was established by echocardiography. The woman did not obtain proper therapy since she was not aware of her cardiac problem during her pregnancy. There were no fetal abnormalities found during prenatal exams. At 38 weeks gestation, an IUD-assisted cesarean surgery was scheduled. While a cesarean section is performed on individuals with certain problems, the majority of CHD cases may be successfully delivered vaginally. Another crucial factor to take into account is the choice of postpartum contraception. Conclusion: A personalized strategy is needed to manage congenital heart disease throughout pregnancy. This includes risk education, careful observation, and modification of interventions to guarantee the best possible results for both mother and child.